GUIDELINES FOR AIDS INTERNET ASSIGNMENT - Anderson, Peter (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Compare and contrast the information you find on AIDS or HIV disease from three different sites you visit on the Internet.